Remote Sensing Quantitative Research on Soil Erosion in the Upper Reaches of the Minjiang River - Bing, Deng; Lei, Shi (Frontiers in Earth Science, 2022)
The upper reaches of the Minjiang River is an important ecological barrier in the upper reaches of the Yangtze River and Chengdu Plain. They are also the water resource of Chengdu Plain. To protect the headwater ecosystems, it is necessary to carry out a quantitative research of soil erosion in this area. This paper mainly applies USLE model to quantitatively evaluate the spatial distribution of ecosystem services on soil erosion and soil conservation. The evaluation is based on the following data: remote sensing image, meteorological radiation data, DEM, soil types, physical and chemical properties of the soil, vegetation types and land use status. With advanced earth observation technology, satellite remote sensing images about terrestrial vegetation and other evaluation parameters can be obtained in real time. The seasonal changes in vegetation coverage and the physical and chemical properties of in the soil have been fully considered. The results show that: (1) The value of rainfall erosivity factor (R) is between 85.02-588.69MJ•mm/(hm2•h•a), and its spatial distribution is consistent with that of annual average precipitation. (2) Soil erodibility factor (K) is between 0.12-0.30 (t·hm2·h) •(hm2·MJ·mm), showing zonal distribution and is related to soil types. (3) Slope length and gradient factor (LS) ranges from 0.03 to 46.16. It is positively correlated with the topographic relief. (4) Soil conservation measure factor (P) ranges from 0 to 1 and is determined by the land use and coverage. (5) Rainfall has a dominant impact on soil erosion, and the study area with violent and intense erosion reaches 17302.17km2, accounting for 69.81% of the total area. The soil conservation amount (T) in the study area is 283.45 million tons, and the ecosystem services are worth 434.48 million yuan. (6) RS and GIS technique enable a quick estimation. However, this assessment contains considerable uncertainty. It is still hard to reveal the physical process of soil erosion with empirical models.